PENERAPAN MODEL PEMBELAJARAN PROBING PROMTING LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN IPA - Encep Andriana; Nana Hendracipta; Siti Gumanti (LPPM Universitas Bina Bangsa, 2023)
The application of the probing prompting learning model to students' critical thinking skills in science subjects. A quasi-experimental study with a non-equivalent control group design. The research was conducted at SD Negeri Sumur Peuteuy. The sampling technique used was purposive sampling. In this study, class IV A was used as the experimental class and class IV B as the control class. This study aims to determine whether there are differences in students' critical thinking skills using the probing prompting learning model and students using the direct learning model. The purpose of the data analysis technique is to test the hypothesis using two tests and the right-hand side test. Based on the two-party hypothesis, tcount = 4,599 and ttable 2,010 so 4,599 > 2,010, meaning Ho is rejected and Ha is accepted. From this research, it can be said that the learning model applied in the experimental class (probing prompting learning model) and in the control class (direct learning model) shows the students' critical thinking skills. And the experimental class is better than the control class